TRAINING OF KAHOOT! AS AN INTERACTIVE GAME-BASED LEARNING EVALUATION PLATFORM FOR STUDENTS - Army Justitia; Badrus Zaman; Rimuljo Hendradi; Fitri Retrialisca; Roslinda Salim (Darmabakti Cendekia: Journal of Community Service and Engagements, 2021)
Background: Maintaining student motivation, involvement and consistency in a learning process is a challenge that must be faced by teachers / educators. Especially during the COVID-19 pandemic, this limits learning activities in online form. Teachers / educators need additional skills to be able to manage classes, deliver material and maintain student motivation. Objective: This community service aims to improve the skills of teachers / educators to provide interactive learning and evaluation media based on game learning. Methods: The methods used in this community service activity were training and focus group discussions. Furthermore, the participants prepared the Kahoot quiz material independently according to the subjects they were teaching them. Result: The result of this training activity is an increase in the skills of teachers / educators in mastering Kahoot, and an increase in teacher / educator understanding of the Kahoot material. This can be seen from the occasional increase of 15.97% after the training was completed. The training participants were satisfied with the implementation of the training as evidenced by filling out the feedback questionnaire, with a satisfaction score above 3.5 out of 4. Conclusion: This community service has a positive impact on skills and understanding related to the use of Kahoot for interactive learning and evaluation media.